Implikasi Pungutan Pajak Berganda Terhadap Pengenaan Pajak Penghasilan Perorangan Atas Dividen - Maverick Gilang Pranyoto (Faculty of Law, Universitas Airlangga, 2022)
AbstractThe emergence of new policies contained in Law no. 11 of 2020 concerning Job Creation. Provide a series of mechanisms to simplify and/or expedite the process of future investment in Indonesia. This has resulted in several changes in the regulation, especially in this discussion regarding Income Tax on Dividends. Provide several tax incentives in order to achieve the goal of the Indonesian state to be able to increase the rate of economic growth. Incentives will be given on condition that at least 30% of dividends obtained by taxpayers must be reinvested in the territory of Indonesia. The enactment of this provision raises questions about the new provision that there is no double taxation, as well as the settlement of double taxation itself. Therefore, upon the application of this provision, there is still double taxation even though the taxpayer has invested at least 30% of the income on dividends.Keywords: Income Tax; Dividend; Double Tax; Investment. AbstrakMunculnya kebijkan baru yang tertuang dalam Undang-Undang No. 11 Tahun 2020 Tentang Cipta Kerja. Memberikan serangkaian mekanisme untuk mempermudah dan/atau memperlancar proses investasi yang akan datang di Indoneisa. Sehingga menimbulkan beberapa perubahan dalam pengaturannya terkhususnya dalam pembahasan ini perihal Pajak Penghasilan atas Dividen. Memberikan beberapa insetif pajak guna untuk mencapai tujuan negara Indonesia untuk dapat menambah angka pertumbuhan ekonomi. Insentif akan diberikan dengan syarat minimal 30% dividen yang diperoleh wajib pajak harus diinvestasikan kembali diwilayah Indonesia. Berlakunya ketentuan ini menimbulkan pertanyaan dengen ketentuan yang baru tidak ada pungutan pajak berganda, serta penyelesaian atas pajak berganda itu sendiri. Sehingga atas berlakunya ketentuan ini masih terdapat pajak berganda walaupun wajib pajak telah menginvetasikan dengan jumlah minilam 30% dari penghasilan atas dividen. Kata Kunci: Pajak Penghasilan; Dividen; Pajak Berganda; Investasi.